Implementation of Kertowono Tea Production Process Control in Efforts to Create Production Targets at PT Perkebunan Nusantara (PTPN) XII in Lumajang - Emmy Ermawati (International Journal of Accounting and Management Research, 2023)
The purpose of this study was to determine the implementation of the production process and planning process in an effort to achieve production targets at PT Perkebunan Nusantara (PTPN) XII in Lumajang. This type of research is descriptive research with a qualitative approach where the data were obtained from a PT Perkebunan Nusantara (PTPN) XII in Gucialit sub-district, Lumajang district. In this study, data were obtained using interview and documentation methods for PT Perkebunan Nusantara (PTPN) XII employees in Lumajang. The data used are primary and secondary data. The results of this study state that PT Perkebunan Nusantara (PTPN) XII in Gucialit Lumajang has implemented a production process starting from input, transformation, output and feedback. In the planning process for Kertowono tea production to achieve the production target, it is carried out by minimizing the number of defective products, this happens due to irregularities in the production process that are not maximal, even though the production target every year has not been achieved or fulfilled, the company is still trying to achieve the target. production with market demand which continues to increase every year.